A Cohort Replacement of Household Labour Supply in Germany and the UK - Rona Geffen (Comparative Population Studies)
In recent decades, fluctuating unemployment rates and welfare state retrenchment have led to increased levels of economic insecurity in some countries. At the same time, cultural norms and family policies have become more gender-egalitarian. While earlier research related these trends to the decline in the male breadwinner model, little is known about whether recent cohorts who entered adult life against the backdrop of a new socio-economic opportunity structure have established new configurations of household labour supply. Using sequence analysis and cluster analyses across harmonised longitudinal data (GSOEP, BHPS and Understanding Society) for a sample of adults born between 1961 and 1973 in Germany and the United Kingdom (UK), this study introduces an innovative indicator of household labour supply types and new descriptive findings on the cohort replacement of household labour supply in these two countries. Descriptive findings show that recent cohorts in both Germany and the UK are forming more gender-egalitarian households, as reflected by the decline in the male breadwinner model as well as by the rise of 1.5-male breadwinner households in Germany and dual-earner households in the UK. However, the proportion of single and low labour intensity households in recent cohorts has declined in the UK, while there has been no meaningful change in East Germany and a strong increase in West Germany. The evolution of household labour supply types can be attributed to the replacement of cohorts who entered adulthood and established their households under shifting socio-economic contexts and gender ideologies.